1996
DOI: 10.1164/ajrccm.153.2.8564113
|View full text |Cite
|
Sign up to set email alerts
|

IgG subclass deficiencies associated with bronchiectasis.

Abstract: Only a small number of patients with IgG subclass deficiencies (IgGSD) have been observed to have bronchiectasis. Moreover, in the series of patients with bronchiectasis, IgGSD have not been found at any frequency, and the etiology of bronchiectasis remains unclear in 29 to 49% of cases. Serum concentrations of total IgG, IgA, and IgG subclasses as well as pulmonary function were measured in 65 patients (aged: 10 to 74 yr) with bronchiectasis of unknown etiology. An ELISA test was performed to quantify subclas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
1
9

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 19 publications
6
48
1
9
Order By: Relevance
“…We only ascribed severe IgG subclass deficiency to values that fell outside the entire range found in healthy persons, and the low incidence of significant IgG subclass 1, 2, or 3 deficiency in our study (1 patient, Ͻ 1%) is similar to that found in others using the same criteria (2%) (21). Another study using less stringent control data reported a higher incidence of IgG subclass deficiency (48%) (38). Patients found to have only borderline low IgG subclass levels were not classified as immunodeficient unless they had evidence of a functional defect as well, determined by a defective response to immunization.…”
Section: Discussionsupporting
confidence: 85%
“…We only ascribed severe IgG subclass deficiency to values that fell outside the entire range found in healthy persons, and the low incidence of significant IgG subclass 1, 2, or 3 deficiency in our study (1 patient, Ͻ 1%) is similar to that found in others using the same criteria (2%) (21). Another study using less stringent control data reported a higher incidence of IgG subclass deficiency (48%) (38). Patients found to have only borderline low IgG subclass levels were not classified as immunodeficient unless they had evidence of a functional defect as well, determined by a defective response to immunization.…”
Section: Discussionsupporting
confidence: 85%
“…By measuring antibody response to Haemophilus influenza type-b capsular polysaccharide vaccine, they found 48% with deficient responses and low levels of one or more IgG subclasses. Of the 31 with diminished IgG responses, 19 had IgG2 deficiency, two had IgG3 deficiency, three had IgG4 deficiency, and seven had combined subclass deficiencies [16]. Of the 225 children with chronic sinopulmonary infections evaluated by Ozkan et al, 19.1% were found to have antibody deficiencies.…”
Section: Infectionsmentioning
confidence: 95%
“…IgG subclass deficiency, particularly that of IgG2, has been associated with bronchiectasis in children [77]. Given that the incidence of bronchiectasis in patients with IgG subclass deficiency varies widely (anywhere from 4% to nearly 50%), it is difficult to establish a correlation between bronchiectasis and IgG subclass deficiency [65,69,[77][78][79]. In one study, SAD was reported in 58% of patients with idiopathic bronchiectasis [80].…”
Section: Bronchiectasismentioning
confidence: 99%